Open access culture and acceptance of open educational resources in Croatian public universities - Krelja Kurelović, Elena (Array, 2018)
The purpose of this paper is to contribute to the understanding of the open access culture and its impact on the use of Open Educational Resources (OER). There are many examples of using the term “open access culture”, but without giving an explicit description of it. The aim of this research is to offer conceptualization of the open access culture, identify its main components, and determine the impact of this variable on the intention to use and the actual use of Open Educational Resources by the members of public higher education institutions in Croatia. The sample consisted of 427 respondents. Keeping in mind that culture has a significant impact on the behaviour of an individual, but it also manifests itself through this behaviour, the research model will be proposed. The variable “open access culture” will be observed on a personal, professional and organizational level and it will include attitudes, perception, norms and politics towards open access to scientific and educational content and knowledge sharing. For the purpose of this study a questionnaire was prepared. Each part of the variable “open access culture”, as well as the intention to use and the actual use of OER, has been tested using a set of statements with answers on a 5-degree Likert type scale. The respondents have expressed a moderate open access culture. The actual use of OER, as well as the intention to use OER, is also in the middle of measurement scale. In order to achieve the aim of this research, three main hypotheses have been proposed. The results of multiple regression analysis show that the proposed model with predictor variable “open access culture” has a significant prognostic value on the intention to use and the actual use of OER, with a stronger influence on the intention to use OER.